Mechanistic contribution of electroconductive hydroxyapatite–titanium disilicide composite on the alignment and proliferation of cells. (May 2016) - Kumar, A; Nune, KC; Basu, B; Misra, RDK
We elucidate here the mechanistic contribution of a novel electroconductive hydroxyapatite-20 wt.% titanium disilicide (HA–TiSi2 ) composite system in favorably modulating osteoblast functions in relation to the monolithic HA. The higher electrical conductivity of HA–TiSi2 (σDC  ∼ 67.117 ± 3.57 S/m) in comparison to glass sample effectively guided the electroactive myoblast, leading to their significant alignment and proliferation. This favorable behavior is attributed to the formation of small electrochemical cells between HA and TiSi2 phase, which produce a small electric field, directing the electroactive myoblast to migrate and grow in a particular direction. In contrast, no impact of TiSi2 on osteoblast function was observed because of their inability to respond to small electric field. However, the in vitro bioactivity in simulated body fluid indicated the nucleation and growth of apatite crystals. Moreover, in the context of load-bearing capability, the presence of 20 wt.% TiSi2 in HA led to increase in the fracture toughness by ∼100%. This study underscores the effectiveness of HA–TiSi2 in favorably modulating the cellular activity, myoblast in particular.